Effect of titanium nitride nanoparticles on the ultrastructure of the rat lung in the chronic experiment - Yavorovskyi, O.P.; Stechenko, L.O.; Solokha, N.V.; Kryvosheiеva, O.I.; Chukhrai, S.M. (Environment & Health, 2017)
Data of our experimental studies on the detection of the effect of titanium nitride nanoparticles on the body of the operators working with nanofacilities are presented in the article.Objective. We studied the effect of titanium nitride nanopowder on the ultrastructures of the lungs of the experimental animals at the intratracheal introduction in the chronic experiment.Materials and methods. We performed the electronic microscope study of the ultrastructural changes in the lungs of white rats of 170-200 g weight. Material for the study (lungs) was taken within definite terms from the moment of introduction. Ultrathin sections were made on ultratom LKB III (Sweden). They were painted and photographed under electronic microscope PEM-125K at a magnification of 4.8-20 thousand diameters.Results. Ultrastructural analysis of the lungs showed that in 1 day after the introduction of titanium nitride nanoparticles they were identified in the part of alveoli and their effect was directed to the damage of aerohematic barrier; respiratory, alveolar epithelium partially suffered a desquamation. In 7 days an edema of the respiratory epithelium and its detachment from the basal membrane were noted, a number of collagen and elastic fibers were increased. Increase of the observation period to 6 months after the introduction of nanoparticles demonstrated the edema of respiratory epithelium, basal membrane expansion, and proliferation of collagen fibers. Plasma cells, responsible for humoral immunity, were observed in the lumen of the alveoli. Pneumosclerosis was noted in a year after the beginning of the experiment as well. Conclusions. Thus, increase of the period of observation points to the development of pneumosclerosis in lung parenchyma and, as a result, the violations of gas exchange and hemomicrocirculation.
Keywords: titanium nitride nanopowder; plasma cells; pneumosclerosis